In vitro and in vivo antiviral activity of monolaurin against Seneca Valley virus - Su, Bo; Wang, Yingjie; Jian, Shanqiu; Tang, Huaqiao; Deng, Huidan; Zhu, Ling; Zhao, Xiaonan; Liu, Jian; Cheng, Huangzuo; Zhang, Lina; Hu, Youjun; Xu, Zhiwen (Frontiers in Veterinary Science, 2023)
Surveillance of the Seneca Valley virus (SVV) shows a disproportionately higher incidence on Chinese pig farms. Currently, there are no vaccines or drugs to treat SVV infection effectively and effective treatment options are urgently needed. In this study, we evaluated the antiviral activity of the following medium-chain fatty acids (MCFAs) or triglycerides (MCTs) against SVV: caprylic acid, caprylic monoglyceride, capric monoglyceride, and monolaurin. In vitro experiments showed that monolaurin inhibited viral replication by up to 80%, while in vivo studies showed that monolaurin reduced clinical manifestations, viral load, and organ damage in SVV-infected piglets. Monolaurin significantly reduced the release of inflammatory cytokines and promoted the release of interferon-γ, which enhanced the viral clearance activity of this type of MCFA. Therefore, monolaurin is a potentially effective candidate for the treatment of SVV infection in pigs.